Pengaruh Destination Image dan Tourist Atraction terhadap Tourist Satisfaction dan Post Visit Behavioral Intention - eny endah pujiastuti; Sadeli Sadeli; Anisa Destiana (Diploma Travel Business, Faculty of Social and Political Science, Jember University, 2019)
The purpose of this study is to understand the influence between Destination Image, Tourist Atraction, Tourist Satisfaction and Post Visit Behavioral Intention. In this study, a total of 115 effective questionnaires were collected which would then be processed using Structural Equating Modeling (SEM) which was operated using the AMOS application. The results of the study show that 1). Destination image has a significant effect on tourist satisfaction. 2). Tourist attraction has a significant effect on tourist satisfaction. 3). Destination image has a significant effect on the post visit behavior intention. 4). Tourist attraction has a significant effect on the post visit behavior intention. 5). Tourist satisfaction has a significant effect on the post visit behavior intention. 6). Destination image has an indirect effect on post visit intention behavior through tourist satisfaction. 7). Tourist attraction influences indirectly on post visit intention behavior through tourist satisfaction. Based on the results of the research, the research not only provides advice for the government tourism sector, but also provides direction for future research.